2011
DOI: 10.1007/s13577-011-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte marker expression in a human lymphocyte cell line using mouse cardiomyocyte extract

Abstract: Cell transplantation shows potential for the treatment of cardiac diseases. Embryonic stem cells, cord blood and mesenchymal stem cells have been suggested as sources for transplantation therapy. Because of some technical limitations with the use of stem cells, transdifferentiation of fully differentiated cells is a potentially useful alternative. We investigated whether human peripheral blood cells could transdifferentiate into cardiomyocyte. Transdifferentiation was induced in a human B lymphocyte cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…To explain this, it could be said that 5‐aza‐dC is more effective in MSC S differentiation into other cell types (Fukuda, ; Makino et al, ; Wakitani et al, ; Xu et al, ). It seems that in application of 5‐aza‐dC more time is needed to get an acceptable response (Taranger et al, ), and the better results may be obtained by using hyper‐acetylating agents in combination with 5‐aza‐dC (Talaei‐Khozani et al, ; Talaei‐Khozani et al, ; Vojdani et al, ); furthermore, 5‐aza‐dC would be more effective on ESCs markers expression, such as OCT4, SOX2 and Nanog (Hattori et al, ; Talaei‐Khozani et al, ; Tsuji‐Takayama et al, ), and its usage in most of the studies was on cell lines, unlike our study which was on primary cell cultures (Diepeveen et al, ; Håkelien et al, ). Additionally, 5‐aza‐dC at diverse doses exerts various effects on cell morphology and gene expression (Kumar et al, ; Zhou et al, ), and also epigenetic status is varied in dissimilar animal cells (Kang et al, ), and changed with time and with environmental stimulations (Jirtle and Skinner, ; Szyf, ).…”
Section: Discussionmentioning
confidence: 99%
“…To explain this, it could be said that 5‐aza‐dC is more effective in MSC S differentiation into other cell types (Fukuda, ; Makino et al, ; Wakitani et al, ; Xu et al, ). It seems that in application of 5‐aza‐dC more time is needed to get an acceptable response (Taranger et al, ), and the better results may be obtained by using hyper‐acetylating agents in combination with 5‐aza‐dC (Talaei‐Khozani et al, ; Talaei‐Khozani et al, ; Vojdani et al, ); furthermore, 5‐aza‐dC would be more effective on ESCs markers expression, such as OCT4, SOX2 and Nanog (Hattori et al, ; Talaei‐Khozani et al, ; Tsuji‐Takayama et al, ), and its usage in most of the studies was on cell lines, unlike our study which was on primary cell cultures (Diepeveen et al, ; Håkelien et al, ). Additionally, 5‐aza‐dC at diverse doses exerts various effects on cell morphology and gene expression (Kumar et al, ; Zhou et al, ), and also epigenetic status is varied in dissimilar animal cells (Kang et al, ), and changed with time and with environmental stimulations (Jirtle and Skinner, ; Szyf, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the extract from the differentiated cells change that fate of the other cell types [ 8 ]. In addition, it can promote cell reprogramming in somatic cells such as fibroblasts [ 9 ], lymphocytes [ 10 ], and granulosa cells [ 11 ]. Talaei-Khozani et al ., [ 12 ] showed that fibroblasts were also able to express cardiomyocyte markers by extract treatment.…”
Section: Introductionmentioning
confidence: 99%